PENERAPAN MODEL PEMBELAJARAN INQUIRY BASED LEARNING DALAM PEMBELAJARAN IPA TENTANG KEMAGNETAN UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA - Naneh Mulyani (JENTRE, 2023)
This action research is entitled The Application of the Inquiry-based Learning Model in Natural Science Class about Magnetism to Increase Learning Motivation and Learning Outcomes of Class IX.1 MTsN 2 Bekasi City Semester Even, Academic Year 2022/2023. This classroom action research was carried out in 3 (three) cycles with 32 students as research subjects consisting of 15 male students and 17 female students. The objectives of this classroom action research were (1) to increase student learning motivation, and (2) to improve student learning outcomes in science subjects. The results of the study are as follows: first, the increase in learning motivation in the first cycle is 67%, the second cycle is 81.3%, and the third cycle is 88.4%, and the average is 78.9%; meaning that there is an improvement in motivation to learn in an orderly and successful manner. Second, the learning outcomes in cycle I was 84.37% with an average value of 80, cycle II was 87.5% with an average value of 82.06, and cycle III was 100% with an average value of 86.25. The average learning completeness of 90.6% succeeded in exceeding the 75% indicator and the average value of 82.95 succeeded in exceeding the KKM = 75; which means that there is a quite significant increase in student learning outcomes. It can be concluded that the application of the inquiry-based learning model in Natural Science Class about magnetism can improve and enhance learning motivation and student learning outcomes